CD insensitive PMD monitoring for different modulation formats based on RF tone power measurement using an FBG notch filter - Jing Yang; Chee, K.W.L.; Changyuan Yu (2009 7th International Conference on Information, Communications and Signal Processing, 2009)
We propose and demonstrate a technique on chromatic dispersion (CD) insensitive polarization mode dispersion (PMD) monitoring based on RF tone power measurement using a narrow band fiber Bragg grating (FBG) notch filter. By filtering out the optical component at 10-GHz (1/4 of the bit rate) away from the carrier in one sideband, the RF tone generated by beating between the carrier and the component at the other sideband can be measured to monitor the PMD in 40-Gbit/s transmission systems. The PMD monitoring range is increased four times compare with that optical component at 40-GHz away is filtered out. Cost effective photoreceiver with relative narrow bandwidth is used. Besides, the proposed scheme is transparent to modulation format. Numerical simulation results of PMD monitoring for different modulation formats (DPSK, DQPSK and Duobinary) at 40-Gbit/s are shown.